Parenting Styles On Adolescent Psychosomatic Disorder: A Meta Analysis - Mugesh, Kavitha; Ahad, Shaista (Journal of Neonatal Surgery, 2025)
Background: Adolescence is a critical developmental stage marked by rapid physical, emotional, and psychological changes, making individuals particularly vulnerable to psychosomatic disorders. While parenting styles are known to influence adolescent mental health, their specific relationship with psychosomatic symptoms remains underexplored. This study aimed to systematically examine the association between authoritative and neglectful parenting styles and psychosomatic issues in adolescents through a meta-analytic approach. Methods : A meta-analysis was conducted using six peer-reviewed empirical studies published between 2016 and 2022. Data were analyzed using Jamovi software, employing a random-effects model to account for study variability. The standardized mean difference (SMD) was used to quantify the effect size, and heterogeneity across studies was assessed using the I² statistic. Results:Findings revealed that authoritative parenting was significantly associated with a reduction in psychosomatic symptoms such as headaches, fatigue, sleep disturbances, and gastrointestinal problems. In contrast, neglectful parenting showed a positive correlation with increased psychosomatic complaints among adolescents. Substantial heterogeneity was observed (I² = 90.02%), but no publication bias was detected. Conclusion:The results highlight the protective role of authoritative parenting in reducing psychosomatic problems during adolescence. These findings emphasize the importance of promoting emotionally supportive and structured parenting practices in mental health interventions and policy formulation to enhance adolescent psychosomatic well-being